A designathon to collaboratively develop sustainable HIV prevention services for youth with community-based organizations in Nigeria - Titilola Gbaja-Biamila; Oliver Ezechi; Ebenezer Adeoti; Jane Okwuzu; Chiyere Arinze; Lauren Fidelak; Olufunto Olusanya; Ucheoma Nwaozuru; Akeem Lateef; Temitope Ojo; Hong Xian; Tomilola Musari-martins; et al. (PLoS ONE, 2026)
Introduction The engagement of youth in the design of services that promote and increase the uptake of essential services to reduce HIV and other sexually transmitted infections is vital to sustaining these preventive services. The study objective is to identify strategies for sustaining HIV prevention services among Nigerian youth, in partnership with community-based organizations, through a crowdsourced open call and designathon in Nigeria. Materials and methods From February to March 2024, Nigerian youth (ages 14–24) submitted ideas to an open crowdsourcing call on how community-based organizations in Nigeria might sustain HIV self-testing and youth-friendly preventive services for at-risk youth. The submissions were scored in each domain: relevance, novelty, scalability, replicability, potential for sustainability, and promotion of equity and fairness, with an integer score of 1 (low) to 3 (high)(S1). Ten teams were selected to participate in the 72-hour designathon. Both quantitative and qualitative analysis was conducted. The study used thematic analysis and the PEN 3-Cultural Model to categorize qualitative data into six themes. Descriptive statistics were used to calculate participants’ demographic characteristics. Results One hundred and seventy-eight participants submitted entries; 161 were online entries, and 17 were received via WhatsApp. The majority of participants were female (57.1%) and aged 19–23 years (55.0%), with a mean age of 21.7 (±4.1). Most participants were from the southwest of Nigeria (53.8%), had secondary education (68.9%), and were students (67.9%). About one-third of teams (31.1%) indicated collaborating with non-governmental organizations as a promising way to sustain preventive services. Six themes emerged: Adapted Intervention Design and Delivery, Youth Engagement and Education, Organization Setting, Socio-cultural and Community Context, Community Leadership Through Training and Financial Resources, and Sustainment Through Community Collaboration. Conclusion The crowdsourcing contest open call and designathon engaged youth from diverse backgrounds, and it is a practical way to generate solutions from key stakeholders affected by the community’s prevailing health issues. Developing service delivery strategies that engage, educate, and collaborate with youth on HIV prevention could be sustainable. However, this will not be conclusive without implementing them over time to test their feasibility and sustainability.